Perilaku Tidak Etis Akuntan : Melihat dari Persepsi Mahasiswa Akuntansi Politeknik Negeri Malang - Ahmad Mustofa; Kurnia Ekasari; Kartika Dewi Sri Susilowati (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
The purpose of this research was to determine the effect of ethical orientation of idealism and ethical knowledge on the accountant's unethical behavior from the perception of accounting students. This research was conducted to students majoring in accounting at the State Polytechnic of Malang at least Accounting, Management Accounting, and Finance study programs. The data used are primary data in the form of an online questionnaire (google form). This type of research is a quantitative descriptive using SPSS analysis. The population of this study was 439 students with a sample counted 210 respondents using purposive sampling and the Slovin formula with an accuracy rate of 95%. The results of this study indicate that the ethical orientation of idealism does not significantly influence the accountant's unethical behavior, while ethical knowledge has a negative and significant effect on the accountant's unethical behavior. However, the ethical orientation of idealism and ethical knowledge together significantly influence the accountant's unethical behavior